MES Compendium Perfect MES Solutions based on HYDRA - Kletti, Jürgen (Springer Berlin Heidelberg : Vieweg, 2018)
Manufacturing Execution System (MES) is the central part and data hub in a manufacturing environment, connecting ERP and shop floor through horizontal and vertical integration. As a perfect example of modern and Industry 4.0 orientated MES, HYDRA is basically modular structured with plenty of standard functions covering all production areas and departments in a factory, such as machine connectivity, production management, production logistics, quality management, resource management, energy management, and HR. Collecting vast real-time production data is just the very first step, where many MES systems linger about. More important is to analyze and utilize mass production data, turning Big Data into Smart Data. MES Hydra offers various analysis tools and reports for the sake of efficiency and transparency. The authors Kletti, Jürgen, born in 1948, studied electrical engineering at the University of Karlsruhe, specializing in technical data processing. After completing his doctorate, he founded the company MPDV Mikrolab GmbH of which he is a partner and managing director today. In addition, Dr. Kletti lectures on corporate management and is a member of various professional committees. Deisenroth, Rainer, born in 1953, after graduating in technical informatics computer science has worked in various companies in the field of hardware and software development and also in product management. In 1990 he joined MPDV Mikrolab GmbH. Today he works there as Sales Director and member of the executive board. He has published numerous technical papers on the subject of MES.